Distance Education - Birevu Muyinda, Paul (IntechOpen, 2012)
Education has become the number one demanded commodity for social and economic transformation for both developing and developed economies. Thus the number of persons going and returning to school has become too big to be handled by existing brick and mortar learning institutions. Besides, the majority of lifelong learners do not have the time to become full-time students. Distance education is becoming the solution to the aforementioned challenges. It has been defined as the mode of study where the learner is separated in time and space from the institution and tutors providing the tuition.